HOTEL RESERVATION SYSTEM USING WEBSITE BASED RAPID APPLICATION DEVELOPMENT (RAD) METHOD - Rima Tamara Aldisa (Adisam Publisher, 2024)
In the era of all-digital as it is today the importance and need a website to make it easier to make hotel reservations online without having to come directly. Hotel is a company that erects a building intended to provide lodging services. The Hotel has a high occupancy rate is on the edge of the highway. There are problems that need to be discussed, namely the difficulty of hotel customers to make room reservations, the difficulty of customers knowing the type and price of rooms. Customer data archiving is still manual book. The design of Hotel Booking Information System with Rapid Application Development (RAD) method based on the Website here with a view to software development is done in a gradual manner. The black box testing method here is used to test the system. The purpose of this study is to make it easier for customers to search for rooms, and booking hotel rooms online directly without having to come first to the hotel and the purpose for the owner or hotel manager is to process customer data from the beginning of reservation, check in, ordering food or breakfast to check out and can facilitate process of making reports.